Interface a guide for professionals supporting the criminal justice system - Laska, Paul R. (Springer's Forensic Laboratory Science Series, 2011)
A wide variety of professionals find themselves intimately involved in the criminal justice system; firefighters, emergency medical providers, nurses, physicians, public health personnel, environmental professionals, public works personnel, and many others. No previous work has attempted to address the criminal justice system in terms relevant to these professionals. Interface: A Guide for Professionals Supporting the Criminal Justice System explains the system, provides the reader with guidance to documenting incidents so that the data is both of value to the professional in the future and for use by the other components of the system. Further, this volume presents evidence from the aspect of these professionals, their needs in handling evidence, and basics of collection and preservation for those instances where it falls to them to do so. Professionals, not familiar with safety issues outside of their fields of expertise, have been injured or died as a result of exposure to hazards; it also educates them to considerations for their safety when out of their area of comfort. In addition, this book considers the role of the professional as interviewer, and provides basic guidance to this often valuable skill. Finally, Interface attempts to make the professional knowledgeable and comfortable in the courts, especially on the stand, where the professional may appear as a witness or even as an expert.